The Curse of Misty Wayfair - Wright, Jaime Jo (Bethany House, a division of Baker Publishing Group, 2019)
Left at an orphanage as a child, Thea Reed vowed to find her mother someday. Now grown, her search takes her to turn-of-the-century Pleasant Valley, Wisconsin. When the clues she finds lead her to a mental asylum, Thea uses her experience as a postmortem photographer to gain access and assist groudskeeper Simeon Coyle in photographing the patients and uncovering the secrets within. However, she never expected her personal quest would reawaken the legend of Misty Wayfair, a murdered woman who allegedly haunts the area and whose appearance portends death. A century later, Heidi Lane receives a troubling letter from her mother - who is battling dementia - compelling her to travel to Pleasant Valley for ansers to her own questions of identity. When she catches sight of a ghostly woman haunting the asylum ruins in the woods, the long-standing story of Misty Wayfair returns - and with it, Heidi's fear for her own life. As two women across time seek answers about their identities and heritage, they must overcome the threat of the mysterious curse that has them inextricably intertwined.